Convertible Bandstop to Allpass Filter using Defected Ground Structure with Ideal Switch for Millimeter-Wave Band in 5G Application - Othman, Adib; A Majid, Huda; Shairi, Noor Azwan; Al-Fadhali, Najib; Mohd Ibrahim, Imran; Zakaria, Zahriladha; Zainal Abidin, Zuhairiah; A Rahim, Mohamad Kamal; F Esmail, Bashar Ali (International Journal of Integrated Engineering, 2023)
According to this study, a defective ground structure (DGS) with an ideal switch can be used to create a bandstop to allpass filter for 5G applications. The redesigned Hairpin DGS's bandstop and allpass responses are mathematically investigated in this paper. Utilising an ideal switch via open circuit and short circuit conditions on DGS, the convertible filter is operated. Therefore, the filter's performance in terms of return loss, attenuation, and insertion loss is simulated. As a result, the filter operates at 25.875 GHz in open circuit condition with a narrowband (2.16 GHz) bandstop response at 10 dB and a maximum attenuation of 29.5 dB, and at 26 GHz with a wideband allpass response and return loss greater than 10 dB. As a result, the filter is appropriate for 5G applications that use millimeter-wave RF front-end systems